BUJANG DAN DARA DALAM MEMPROMOSIKAN PARIWISATA DI KABUPATEN INDRAGIRI HULU - Yulaichah, Siti; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Indragiri Hulu has attractions that can be enjoyed by the community, in domestically and abroad. In this paper the author only discusses how Bujang and Dara in promoting tourism. The purpose of this study is to determine how Bujang and Dara in promoting tourism in Indragiri Hulu and to identify inhibiting factors Bujang and Dara in promoting tourism in Indragiri Hulu.This study uses the theory of Hamdani to know how sales promotion, public relations, and world of mouth (information by word of mouth). Type of this research is qualitative descriptive method by using purposive sampling technique. This method does not use population and sample, because if the data collected is already deep and explain the phenomenon under investigation, then no need to look for another sampling. While data collection techniques in this research is by using observation, interview and documentation.Based on the results of research and discussion it can be concluded that the Bujang and Dara in promoting tourism in Indragiri Hulu is still in the category has not been optimal. Less maximum budget spending and public ignorance of the contribution of each Bujang and Dara were selected, but it is still no clarity from the manager of that tourist attraction, however the period of position a Bujang and Dara too brief. This is the inhibiting factor in promoting an attraction.Keywords: Tourism, Promotion, Bujang and Dara